2001
DOI: 10.1080/02786820152546761
|View full text |Cite
|
Sign up to set email alerts
|

A Particle-into-Liquid Collector for Rapid Measurement of Aerosol Bulk Chemical Composition

Abstract: We report on a new instrument developed for rapid automated on-line and continuous measurement of ambient aerosol bulk composition. The general approach is based on earlier devices (Khlystov et al. 1995; Simon and Dasgupta 1995) in which ambient particles are mixed with saturated water vapor to produce droplets easily collected by inertial techniques. The resulting liquid stream is analyzed with an ion chromatograph to quantitatively measure the bulk aerosol ionic components. In this instrument, a modi ed vers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
341
0
3

Year Published

2002
2002
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 411 publications
(349 citation statements)
references
References 27 publications
5
341
0
3
Order By: Relevance
“…The PILS collects particles by growing them through 119 exposure to a saturated steam environment and then causing their impaction on a surface. A 120 solution containing aerosol species for injection to the ICs (Dionex ICS 1600) is generated by 121 washing the impaction surface with deionized water (Weber et al, 2001;Orsini et al, 2003 The total observed HR-ToF-AMS PM 1 mass concentration ranged between 1.1 and 16.5 µg 143 m -3 , with a mean of 4.4 ± 2.6 (one s.d.) µg m -3 .…”
Section: Introduction 44mentioning
confidence: 99%
“…The PILS collects particles by growing them through 119 exposure to a saturated steam environment and then causing their impaction on a surface. A 120 solution containing aerosol species for injection to the ICs (Dionex ICS 1600) is generated by 121 washing the impaction surface with deionized water (Weber et al, 2001;Orsini et al, 2003 The total observed HR-ToF-AMS PM 1 mass concentration ranged between 1.1 and 16.5 µg 143 m -3 , with a mean of 4.4 ± 2.6 (one s.d.) µg m -3 .…”
Section: Introduction 44mentioning
confidence: 99%
“…In recent years a range of new ambient aerosol analysis techniques capable of providing quantitative on-line and almost realtime information on the chemical properties of particles has been developed, including on-line ion chromatographic techniques (Weber et al 2001), or thermal evaporation techniques with subsequent gas analysis for sulfate, nitrate, and carbon mass concentration measurements (Stolzenburg and Hering 2000;Allen et al 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Some methods bypass the filters and filter sampler used in the conventional method by collecting the particles directly into a liquid medium (Buhr et al, 1995;Khlystov et al, 1995;Liu and Dasgupta, 1996;Karlsson et al, 1997;Ito et al, 1998;Weber et al, 2001). These methods avoid the collection and extraction steps and their associated problems, although they typically employ a similar analytical technique, IC.…”
Section: Introductionmentioning
confidence: 99%